From Global Financial Crisis to post-COVID: Mapping the transition in Sukuk research - Ali, Hassnian; Jafar, Ahmad (Universitas Islam Indonesia, 2024)
IntroductionThe financial sector has experienced substantial changes throughout history, and sukuk has gained widespread recognition as a reliable funding option.ObjectivesThis study explores the evolution and impact of Sukuk financing from the Global Financial Crisis to the post-COVID era, emphasizing its importance within Islamic finance and its broader economic implications.MethodUsing a bibliometric analysis approach, data were extracted from the Scopus database, focusing on 287 English-language research articles containing